Tubeless versus tubed percutaneous nephrolithotomy for treating kidney stones - Wilhelm, Konrad (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects and efficacy of tubeless mini percutaneous nephrolithotomy versus standard percutaneous nephrolithotomy for the treatment of renal stones in adults.